DIFFERENTIAL SPECTRUM OF SPEECH IN-FORMATION - Hryshchuk, Olha (Ukrainian Information Security Research Journal, 2023)
In the conditions of widespread availability of communication systems, each of the subscribers of information exchange in most cases seeks to achieve maximum confidentiality during mutual communication. To meet this need, a number of the latest technologies for the protection of speech information have been developed and implemented in the world. For example, the simplest software and hardware means of protecting speech information in the form of scramblers are known, or more advanced software means of stream encryption in public messengers WhatsApp, Signal, etc. Means of cryptography security of speech information are also widely used in radio stations such as Motorola, Hytera, etc. The issue of ensuring the confidentiality of speech information in special purpose communication systems is one of the key requirements for such type systems. Despite the technologies used to ensure the confidentiality of speech information, the number of attempts to gain unauthorized access to it is constantly increasing, so the issue of ensuring its security is currently relevant. In this article, on the basis of previously known research, it is proposed to present speech information in the form of a differential spectrum based on its harmonic model. The differential spectrum of speech information is obtained on the basis of differential transformations of Academician of the National Academy of Sciences of Ukraine H. Pukhov. To ensure the given precision of speech information restoration in real time, the minimum required number of differential spectrum discretes was substantiated. It is shown and proven that the differential spectrum of speech information considered in the article is the basis for its use in an alternative system of encryption of speech information with guaranteed cryptographic resistance - the Fredholm's cryptosystem. The obtained results can be generalized to gain differential spectrums of speech information, provided by other models, other than the harmonic model considered in the article.